Penguatan Moderasi Beragama Remaja Kampung Pancasila melalui Diseminasi ”Semai Sirama” - Mahfud, Muhammad; Mulyadi, Mulyadi; Pertiwi, Aulia Hana; Sofiyah, Siti (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
The present study addresses the rising phenomenon of religious intolerance and polarization among the youth, highlighting the urgent need for religious moderation as a national foundation. The current inquiry discusses a youth empowerment program centered on the dissemination of